1996
DOI: 10.2337/diab.45.10.1435
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Cortisol Promote Leptin Production in Cultured Human Fat Cells

Abstract: The aim of this study was to investigate the regulation of leptin expression and production in cultured human adipocytes using the model of in vitro differentiated human adipocytes. Freshly isolated human preadipocytes did not exhibit significant leptin mRNA and protein levels as assessed by reverse transcriptase (RT)-polymerase chain reaction (PCR) and radioimmunoassay (RIA). However, during differentiation induced by a defined adipogenic serum-free medium, cellular leptin mRNA and leptin protein released int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
167
2
14

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(197 citation statements)
references
References 24 publications
14
167
2
14
Order By: Relevance
“…did not shift the peak and nadir timing of leptin). These results are consistent with previous findings that glucocorticoids stimulate leptin secretion or ob mRNA expression in adipose tissue [13, 14, 15, 16, 18], and exogenous glucocorticoid increased the concentration of circulating leptin in vivo [17, 18, 19]. Therefore, it is suggested that diurnal rhythm of cortisol does not play an essential role in generating leptin diurnal rhythm, but suggests that glucocorticoids modulate the leptin diurnal rhythm (mostly its amplitude).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…did not shift the peak and nadir timing of leptin). These results are consistent with previous findings that glucocorticoids stimulate leptin secretion or ob mRNA expression in adipose tissue [13, 14, 15, 16, 18], and exogenous glucocorticoid increased the concentration of circulating leptin in vivo [17, 18, 19]. Therefore, it is suggested that diurnal rhythm of cortisol does not play an essential role in generating leptin diurnal rhythm, but suggests that glucocorticoids modulate the leptin diurnal rhythm (mostly its amplitude).…”
Section: Discussionsupporting
confidence: 82%
“…Glucocorticoids are potent stimulators of leptin secretion [13, 14, 15, 16, 17, 18, 19], and there is a reciprocal temporal relationship between circulating leptin and glucocorticoids [5, 20, 21]. The nocturnal increase in leptin, when compared as 24-hour secretory profiles, closely resembles the early morning rise of cortisol [4].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that leptin production by adipocytes can be influenced by several hormones. Testosterone and catecholamines inhibit leptin secretion [3, 4, 5], while insulin and cortisol stimulate its secretion by adipocytes [6, 7]. Studies on the in vivo secretion of leptin are still scarce, although the data are consistent with the in vitro findings [8].…”
Section: Introductionsupporting
confidence: 70%
“…Apart from promoting glycogenolysis, it remains inconclusive whether leptin may act in part to induce hyperglycemia through gluconeogenic pathways. Previous studies have shown that cortisol increases leptin synthesis and secretion in human adipocytes (Wabitsch et al 1996), with leptin, in turn, suppressing the hypothalamic-pituitary-interrenal axis in both fish and humans (Szücs et al 2001. In the present study, we demonstrated that cortisol upregulates the expression of lepr in the liver of tilapia (Fig.…”
Section: Discussionmentioning
confidence: 99%